If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7.9x + 1 = 6.9x Reorder the terms: 1 + 7.9x = 6.9x Solving 1 + 7.9x = 6.9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6.9x' to each side of the equation. 1 + 7.9x + -6.9x = 6.9x + -6.9x Combine like terms: 7.9x + -6.9x = 1x 1 + 1x = 6.9x + -6.9x Combine like terms: 6.9x + -6.9x = 0.0 1 + 1x = 0.0 Add '-1' to each side of the equation. 1 + -1 + 1x = 0.0 + -1 Combine like terms: 1 + -1 = 0 0 + 1x = 0.0 + -1 1x = 0.0 + -1 Combine like terms: 0.0 + -1 = -1 1x = -1 Divide each side by '1'. x = -1 Simplifying x = -1
| 1/2x+2=(4x+1)/4 | | 18.1=p-7 | | v-9.85=6.4 | | 1/2x+2=4x+1/4 | | 27=2a+5 | | 10-x=17 | | 2xy+3yz=-5xz-2xy | | 4z-9z+2=0 | | -(8y+1)-(-7y-5)=5 | | x=-5x^2+6x+9 | | y(x)=-16x^2+64x | | a=2a+(-3) | | 500t=1000/300 | | x=-5x^2+8x+9 | | x^3+x^2+3*x+5=0 | | 2x-(5a+7x)=8x+(-3x+7a)-2a | | 3=j+2 | | f(x)=-5x^2+8x+9 | | 15(m+5)-3(8m+7)= | | 125x^2=12 | | -x^2-6x-8= | | -1=-5+I | | 6+2r-3=6r+3-3r | | 3[7x-2(y-1)]= | | 2=H-4 | | 2=H+4 | | u-1/8 | | -3x^2-6x-8= | | m^2-2*m+2=0 | | 4(x-2)-6(9x+7)= | | z^2-11z+19=-5 | | u-2/4 |